Comparison of inflammatory biomarker levels in neurodegenerative proteinopathies: a case-control study - Cook, Sarah E. V.; Menšíková, Kateřina; Koníčková, Dorota; Šlanhofová, Hedvika; Klíčová, Kateřina; Raška, Milan; Zapletalová, Jana; Friedecký, David; Kaňovský, Petr (Journal of Neural Transmission, 2025)
While diagnostic criteria have been established and validated for most neurodegenerative diseases, the considerable overlap between individual nosological entities remains a significant diagnostic challenge. Increasing evidence suggests that neurodegeneration is often initiated by inflammation within the central nervous system. The identification of inflammation could serve as a first signal of the pathophysiological process. As such, validated biological markers (“biomarkers”) of neuroinflammation are critically important. This study aimed to assess the presence and levels of inflammatory biomarkers in three neurodegenerative diseases: Lewy body diseases (LBD), multiple system atrophy (MSA), and 4-repeat tauopathies (4RT). A total of 83 LBD, 24 MSA, and 31 4RT patients were included, with 83 control subjects for comparison. Six immune-related proteins were analysed in cerebrospinal fluid (CSF) and blood serum (serum): C3 complement, C4 complement, haptoglobin, transferrin, orosomucoid, and β2 microglobulin (β2M). ANCOVA statistical analysis revealed significantly lower levels of several inflammatory biomarkers in LBD (CSF: transferrin, C3 complement, orosomucoid; Serum: orosomucoid, β2M) and MSA (CSF: transferrin, C3 complement, C4 complement, orosomucoid) compared to controls. Significant differences were also observed between the synucleinopathy patient groups (LBD and MSA) and 4RT in serum levels of C3 complement. Additionally, the CSF/serum quotients for transferrin (LBD and MSA) and C3 complement (LBD) were significantly lower in disease relative to controls. These findings suggest that inflammatory processes may play a role in the pathophysiology of neurodegenerative proteinopathies, warranting further research to confirm these associations. The identification of potential fluid biomarkers would then represent a promising step forward in the field.